Metal‐Mediated Interactions in Homo‐ and Heterobimetallic Edifices with Lanthanides: A Study in Solution. Issue 26 (1st September 2022) - Hamacek, Josef; Elhabiri, Mourad; Le Guennic, Boris; Shanzer, Abraham; Albrecht‐Gary, Anne‐Marie
Abstract: We report here on the coordination properties of a series of lanthanide cations (Ln=La, Nd, Eu, Tb, Er) with a tripodal homoditopic ligand L, which is bearing three diamido‐dihydroxamate arms anchored on a tertiary amine. The complexes of L with lanthanides were studied in a MeOH/H2 O (80/20 by weight) solvent and a marked size‐discriminating effect depending on the intramolecular interactions was observed in the tripodal dinuclear lanthanide edifice. Positive cooperative effects favour the formation of the bimetallic L Ln2 complexes compared with the monometallic analogues for the heavier lanthanide cations (Eu, Tb, Er), while the lighter ones (La, Nd) show a decrease of cooperative interactions in the corresponding bimetallic species. Moreover, increased levels of heterobimetallic complexes are detected for Ln(III) pairs containing a lighter Ln(III) ion and a heavier one. In contrast with the adjunctive ligand exchange reported for L Fe2 and CDTA, the corresponding substitution reaction for L Ln2 occurs according to a disjunctive mechanism. Our work thus highlights the importance of the balance between the rigidity of a tripodal structure and the flexibility of the side arms to accommodate two trivalent cations in a supramolecular ensemble. Abstract : Self‐assembly of homo‐ and heteronuclear complexes between a ditopic tripodal ligand and selected lanthanides was investigated with spectrophotometry and ESMS. Strong positive cooperativity in favor of dinuclear C3 ‐symmetrical podands and a size‐discrimination along the series are revealed using the site‐binding thermodynamic model.